EVALUATION OF CAPTURING ARCHITECTURALLY SIGNIFICANT REQUIREMENTS METHODS - B, SATHIS KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Every software development organization strives for customer satisfaction. It is universally accepted that the success of software development lies in the clear understanding of the client requirements. During requirement elicitation and analysis stage, the system analyst identifies the functional and non-functional requirements from the customer. Security, usability, reliability, performance, scalability and supportability are the significant quality attributes of a software system. These quality attributes are also referred as non-functional requirements. Only a few functional and quality attributes requirement help to identify and shape the software architecture. A software system’s architecture is the set of prime design decisions made about the system. If the requirement influences the architectural design decision then, it is referred as Architecturally Significant Requirement (ASR). Identifying and specifying all the possible ASR are important tasks in the requirement elicitation and analysis stage.In this research, general problems that are faced while capturing and specifying ASR in requirement elicitation and analysis is studied. Among the different requirement elicitation techniques, use case diagram has been identified and enhanced to solve the problem of capturing and specifying ASR during the requirement elicitation and analysis phase Â 